2008
DOI: 10.1103/physrevlett.101.085901
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Thermal Conductivity in Highly Anion-Defective Aluminates

Abstract: Ultralow thermal conductivity (1.1 W/m.K, 1000 degrees C) in anion-deficient Ba2RAlO5 (R=Dy, Er, Yb) compounds was reported. The low thermal conductivity was then analyzed by kinetic theory. The highly defective structure of Ba2RAlO5 results in weak atomic bond strength and low sound speeds, and phonon scattering by large concentration of oxygen vacancies reduces the phonon mean free path to the order of interatomic distance. Ba2DyAlO5 exhibits the shortest phonon mean free path and lowest thermal conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 22 publications
3
65
0
Order By: Relevance
“…Figure 1b indicates that YSZ could significantly reduce the thermal conductivity of Nb-STO polycrystalline ceramics. Furthermore, we measured both longitudinal (V L ) and transverse sound velocities (V S ) of the samples by an ultrasonic pulse-echo method, which allowed the mean phonon velocity (V M ) 9 and phonon mean free path (L phonon ) 10,11 to be evaluated according to the following equations:…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1b indicates that YSZ could significantly reduce the thermal conductivity of Nb-STO polycrystalline ceramics. Furthermore, we measured both longitudinal (V L ) and transverse sound velocities (V S ) of the samples by an ultrasonic pulse-echo method, which allowed the mean phonon velocity (V M ) 9 and phonon mean free path (L phonon ) 10,11 to be evaluated according to the following equations:…”
Section: Resultsmentioning
confidence: 99%
“…Recently Wan et al 28 have reported that an oxygen deficient aluminium oxide Ba 2 DyAlO 5 exhibits a low value of close to 10 mW/cmK at 1000…”
mentioning
confidence: 99%
“…On the other hand, the behavior of thermal conductivity and thermal diffusivity of nanocomposite materials is still a matter of debate in the literature [25,26]. Some of the most investigated systems are the so called nanofluids (metallic or semiconductor nanocrystals in liquid solvents, like water, ethanol and others), where surprising increases in the thermal diffusivity have been reported with a small addition of metallic nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…k is limited by anharmonic interactions with other phonons or scattering with imperfections, electrons or impurities. As D is related to K by D=K/qC where q is the density, then D=v s k/3q [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%